Evaluation of Measured Strain Responses to in Situ Vehicular Loading for Typical Asphalt Pavements - XIAO, Chuan (Engineering Transactions, 2019)
To characterize the dynamic behavior of typical asphalt pavements, which is induced by a complex loading system coupled with environmental effects, full-scale field tests were conducted on instrumented sections with embedded sensors. The impacts of vehicular loading factors and pavement temperature on strains at the bottom of asphalt layers were analyzed in the presence of in situ dynamic loading. According to orthogonal array tests, the impact levels of loading factors were quantified through analysis of variance. Furthermore, the temperature conversion factors of measured strain were explored using regression analysis. These results show that the measured strains present an asymmetry over time. The strain response goes up with increasing axle load and decreases with growing speed. Compared to the speed and the tire inflation pressure, the axle load plays a dominant role in strain responses. The estimated temperature conversion factor facilitates the strain conversion between non-standard temperature conditions and a required reference temperature.